Allelopathy and Identification of Five Allelochemicals in the Leaves of the Aromatic Medicinal Tree Aegle marmelos (L.) Correa - Seinn Moh Moh; Shunya Tojo; Toshiaki Teruya; Hisashi Kato-Noguchi (Plants, 2024)
Aegle marmelos (L.) Correa is an economically and therapeutically valuable tree. It is cultivated as a fruit plant in southeast Asian countries. In this research, we investigated the allelopathy and possible allelochemicals in the leaves of A. marmelos. Aqueous methanol extracts of A. marmelos exhibited significant inhibitory effects against the growth of Lepidium sativum, Lactuca sativa, Medicago sativa, Echinochloa crusgalli, Lolium multiflorum, and Phleum pratense. Bioassay-directed chromatographic purification of the A. marmelos extracts resulted in identifying five active compounds: umbelliferone (1), trans-ferulic acid (2), (E)-4-hydroxycinnamic acid methyl ester (3), trans-cinnamic acid (4), and methyl (E)-3’-hydroxyl-4’-methoxycinnamate (5). The hypocotyl and root growth of L. sativum were considerably suppressed by these compounds. Methyl (E)-3’-hydroxyl-4’-methoxycinnamate also suppressed the coleoptile and root growth of E. crusgalli. The concentrations of these compounds, causing 50% growth reduction (I50) of L. sativum, were in the range of 74.19–785.4 μM. The findings suggest that these isolated compounds might function in the allelopathy of A. marmelos.